In ∆ABD,
∠D = 90°
and ∠B is acute
∠D > ∠B
∴ AB > AD ...(1)
| Side opposite to greater angle is longer
In ∆ACD,
∠D = 90° and ∠C is acute.
∴ ∠D > ∠C
∴ AC > AD ...(2)
| Side opposite to greater angle is longer Adding (1) and (2), we have
AB + AC > 2AD ...(3)
Similarly, we can prove that,
BC + BA > 2BE ...(4)
| ∵ BE AC
and CA + CB > 2CF ...(5
| ∴ CF AB
Adding (3), (4) and (5), we get
⇒ 2(AB + BC + CA) > 2(AD + BE + CF)
⇒ AB + BC + CA > AD + BE + CF
⇒ AD + BE + CF < AB + BC + CA.
[Hint. Produce AD to E such that AD = DE and join C and E.]
OR
Prove that the sum of any two sides of a triangle is greater than twice the length of median drawn to the third side.
Prove that the sum of the three sides of a triangle is greater than the sum of its three medians.
OR
Prove that the perimeter of a triangle is greater than the sum of its three medians.